BULLING BEHAVIOURS, SELF-ESTEEM AND ACADEMIC ACHIEVEMENT AMONG JORDANIAN SCHOOL STUDENTS - Rshaid, Abdullah M Bani (PEOPLE: International Journal of Social Sciences, 2019)
This study investigated the differences among bullies, victims and uninvolved in self-esteem and academic achievement. The sample of the study consisted of 641 students (303 males, 338 females) in grades from seventh to tenth. For achieving the aim of this study, the following scales were used: bullying scale, victimization scale, self-esteem scale, and GPAs. The results showed that both Univolved students and bullies had significantly higher self-esteem than did victims. Univolved students had significantly higher academic performance than did bullies or victims. Implications were discussed.